2024
DOI: 10.1080/15384047.2024.2322206
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside inhibited the proliferation of gastric cancer cells through up-regulating tumor suppressor miR-1343-3p and down-regulating MAP3K6/MMP24 signal molecules

Xiaoping Wang,
Zhendong Zhang,
Xiaolan Cao

Abstract: Salidroside inhibited the proliferation of cancer cell. Nevertheless, the mechanism has not been completely clarified. The purpose of the study is to explore the mechanisms of salidroside against gastric cancer. To analyze the changes of microRNA (miRNA) in gastric cancer cells under the treatment of salidroside, the miRNA expression was analyzed by using RNA-seq in cancer cells for 24 h after salidroside treatment. The differentially expressed miRNAs were clustered and their target genes were analyzed. Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Interestingly, agents that suppress GC tumour growth also affect the expression of miRNAs. For example, Wang et al [143] demonstrated that salidroside, a metabolite of Rhodiola, arrested the cell cycle and enhanced apoptosis of GC cells. Furthermore, the authors found that the treatment stimulated the expression of the tumour suppressor miR-1343-3p.…”
Section: The Role Of Micrornas In the Pathogenesis Of Gastric Cancer ...mentioning
confidence: 99%
“…Interestingly, agents that suppress GC tumour growth also affect the expression of miRNAs. For example, Wang et al [143] demonstrated that salidroside, a metabolite of Rhodiola, arrested the cell cycle and enhanced apoptosis of GC cells. Furthermore, the authors found that the treatment stimulated the expression of the tumour suppressor miR-1343-3p.…”
Section: The Role Of Micrornas In the Pathogenesis Of Gastric Cancer ...mentioning
confidence: 99%